Factors Affecting Germination Behaviour of Teak Seeds of Eighteen Indian Origins - Gupta, B. N.; Pattanath, P. G. (Indian Forester, 1973)
Results of the investigation indicate that the physiological condition in the form of nutrient imbalance is an important cause of dormancy in teak seeds. Fertility index of the site appears to have even a more pronounced effect on the seed behavior than precipitation, and it was seen that teak seeds from dry areas were in some cases easier to germinate than those from moist areas. The presence of a water soluble germination inhibitor in the mesocarp also appears to play an important role in dormancy. In additicn to this, many origins also exhibit the phenomenon of after-ripening which is the cause of delayed germination and this aspect needs farther study.